Hubungan antara self -regulated learning dengan perilaku cyberloafingpada mahasiswa di pusat kegiatan mahasiswa (PKM) - Leko Albiko; Rahayu Hardianti Utami (Jurnal Riset Psikologi, 2024)
The motivation for this research is the problem of the relationship between students’ cyberloafing habits and self -regulated learning in student activity centersFinding out how big the relationship is between students' cyberloafing behavior and their ability to self-regulate learning is the main motivation of this research. This research uses statistical methods and is quantitative in nature. Examining the relationship between cyberloafing and self-regulated learning was the goal of this study's correlational research technique. By using a sampling approach, the research sample consisted of 100 respondents. Likert scale questionnaires that have gone through validity and reliability tests were distributed to collect data for this research. SPSS 25.00 was used to process the data. On a metacognitive scale of 80%, self-regulated learning is in the medium category; motivation is at 72%. On the other hand, behavior is in the high category at 75%, while cyberloafing is in the low category at 70%. Research findings show that among students at the Padang State University Student Activity Center, self-regulated learning and cyberloafing activities are positively correlated.